The value of comparative research in major day surgery - Alba Llop-Gironés; Montse Vergara-Duarte; Josep Anton Sánchez; Gemma Tarafa; Joan Benach (Elsevier, 2018)
Objective: To measure time trends in major day surgery rates according to hospital ownership and other hospital characteristics among the providers of the public healthcare network of Catalonia, Spain. Method: Data from the Statistics of Health Establishments providing Inpatient Care. A generalized linear mixed model with Gaussian response and random intercept and random slopes. Results: The greatest growth in the rate of major day surgery was observed among private for-profit hospitals: 42.9 (SD: 22.5) in 2009 versus 2.7 (SD: 6.7) in 1996. These hospitals exhibited a significant increase in major day surgery compared to public hospitals (coefficient 2; p-value <0.01) Conclusions: The comparative evaluation of hospital performance is a decisive tool to ensure that public resources are used as rationally and efficiently as possible. Resumen: Objetivo: Medir la evolución temporal de la cirugía mayor ambulatoria entre los proveedores de la red sanitaria pública de Cataluña de acuerdo con la titularidad y otras características de los hospitales. Métodos: Con datos provenientes de la Estadística de Establecimientos Sanitarios con Régimen de Internamiento, se realizó un modelo lineal generalizado mixto con respuesta gaussiana y pendiente e intersección aleatorios. Resultados: Se observó que la mayor variación en la tasa de cirugía mayor ambulatoria era para los hospitales privados con fines de lucro: 42,9 (desviación estándar [DE]: 22,5) en 2009 frente a 2,7 (DE: 6,7) en 1996. Estos hospitales tuvieron un aumento significativo de la cirugía mayor ambulatoria en comparación con los hospitales públicos (coeficiente 2; p <0,01). Conclusiones: La evaluación comparativa del desempeño de los hospitales es una herramienta decisiva para garantizar que los recursos públicos se utilizan de la forma más racional y eficiente posible. Keywords: Health services research, Ambulatory surgical procedures, Public Hospitals, Private Hospitals, Palabras clave: Investigación sobre servicios de salud, Procedimientos quirúrgicos ambulatorios, Hospitales públicos, Hospitales privados